1998
DOI: 10.1023/a:1006039016393
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A protein associated with citrus blight (CB), a disease of unknown cause, was partially characterized. The 12 kDa protein, designated p12, is diagnostic of CB and is present in leaves and xylem fluid from roots and stems of CB-affected trees. The protein, and up to six other CB-specific proteins, are readily detected by SDS-PAGE of xylem fluid from CB-affected trees. The partial N-terminal amino acid sequence of p12 was found to be unique based on database searches. A cDNA library from CB-affected root cambium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Using MS/MS sequence tags, we identified the coding sequence for this protein in the TIGR tomato gene index. XSP10 is very different from the few proteins thus far identified in xylem sap of various plants [5–7,9,10] and represents a new class of small, cysteine‐rich plant‐specific proteins bearing a structural relationship to plant LTPs (Figs. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using MS/MS sequence tags, we identified the coding sequence for this protein in the TIGR tomato gene index. XSP10 is very different from the few proteins thus far identified in xylem sap of various plants [5–7,9,10] and represents a new class of small, cysteine‐rich plant‐specific proteins bearing a structural relationship to plant LTPs (Figs. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…In cucumber xylem sap, several of these have been identified as glycine‐rich proteins, a lectin‐like protein and a chitinase [5–7]. In addition, new proteins appear in xylem sap during development of diseases affecting the vascular system [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…It may appear quite counterintuitive that PNPs (including immunoreactant PNPs) are up-regulated in the host in response to pathogen attack [12,66], while at the same time the pathogen gains an advantage by using this molecule to its own advantage. However, it does appear that plant hormone responses are highly complex and triggered and/or modulated by specific ratios of different hormones and signaling molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the 12 kDa protein revealed that it belonged to the gamma-expansin family [29], showing homology with tree-members of this family. Expansins refer to a family of non-enzymatic proteins found in the plant cell wall [30], and which includes small proteins grouped in two large (alpha and beta-expansins) and two small (gamma-, and epsilon- expansins) subfamilies [31].…”
Section: Discussionmentioning
confidence: 99%